2016
DOI: 10.1158/0008-5472.can-15-0561
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Targeting of Tumor-Derived R-Spondin Attenuates β-Catenin Signaling and Tumorigenesis in Multiple Cancer Types

Abstract: Deregulation of the b-catenin signaling has long been associated with cancer. Intracellular components of this pathway, including axin, APC, and b-catenin, are frequently mutated in a range of human tumors, but the contribution of specific extracellular ligands that promote cancer development through this signaling axis remains unclear. We conducted a reporter-based screen in a panel of human tumors to identify secreted factors that stimulate b-catenin signaling. Through this screen and further molecular chara… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
104
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(112 citation statements)
references
References 50 publications
8
104
0
Order By: Relevance
“…Fourth, inhibition of the growth of the HBCx-60 RSPO2 -overexpressing metaplastic TNBC PDX by IWR-1 strongly suggests that the positive effect of RSPO2 on breast tumour growth is dependent on its ability to stimulate the activity of the Wnt/ β -catenin pathway. Our hypothesis that RSPO overexpression could stimulate breast carcinogenesis by inducing Wnt/ β -catenin pathway activity is strongly supported by recent studies showing that inhibition of RSPO by specific antibodies attenuates β -catenin signalling and tumorigenesis in multiple cancer types (ovarian cancer for RSPO1 , colon and pancreatic cancer for RSPO2 , non-small lung cancer, colorectal and ovarian cancer for RSPO3 ; Chartier et al , 2016). …”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Fourth, inhibition of the growth of the HBCx-60 RSPO2 -overexpressing metaplastic TNBC PDX by IWR-1 strongly suggests that the positive effect of RSPO2 on breast tumour growth is dependent on its ability to stimulate the activity of the Wnt/ β -catenin pathway. Our hypothesis that RSPO overexpression could stimulate breast carcinogenesis by inducing Wnt/ β -catenin pathway activity is strongly supported by recent studies showing that inhibition of RSPO by specific antibodies attenuates β -catenin signalling and tumorigenesis in multiple cancer types (ovarian cancer for RSPO1 , colon and pancreatic cancer for RSPO2 , non-small lung cancer, colorectal and ovarian cancer for RSPO3 ; Chartier et al , 2016). …”
Section: Discussionsupporting
confidence: 63%
“…The difficulty of detecting the RSPO proteins by western blotting is a well-known problem in the literature (Seshagiri et al , 2012; Chartier et al , 2016). We first examined RSPO mRNA expression in a series of 446 breast tumours, including 68 TNBC.…”
Section: Resultsmentioning
confidence: 99%
“…30 The expression levels of N-cadherin, vimentin, and snail in AGS cells were all decreased, suggesting that RSPO2 inhibition enhances epithelial cell characteristics Several signal pathways and complex molecular mechanisms underlie EMT occurrence and regulation, such as tumor growth factor-β, Notch, RTK/Ras, nuclear factor -κB, and WNT/β-catenin. 34 As tumor metastasis is the leading cause of treatment failure and death in cancer patients and tumor progression and metastasis are enhanced by tumor microenvironment and EMT, 35 we speculate that RSPO2 may serve as a next-generation therapeutic target for GC. 32 It has been suggested that RSPO2 enhances WNT/ β-catenin signaling to confer stemness-associated traits of pancreatic cancer cells via EMT.…”
Section: Discussionmentioning
confidence: 92%
“…These fusions are exclusive to the more common APC and b-catenin mutations in colorectal cancer, providing strong evidence that the fusions play a role in tumorigenesis. In addition, efficacy has been demonstrated by targeting of RSPOs in patient-derived xenograft (PDX) models selected on the basis of high RSPO expression (22). Because GSK3178022 effectively inhibits both WNT and RSPO stimulation in vitro, PDX models with genetically defined RSPO fusions were identified and used for in vivo testing of the efficacy of GSK3178022 to inhibit Wnt signaling and tumor growth.…”
Section: Resultsmentioning
confidence: 99%